Time periodic traveling fronts of pyramidal shapes for periodic Lotka–Volterra competition–diffusion system. (June 2017) - Bao, Xiongxiong
Abstract: This paper is concerned with the time periodic traveling front solutions of pyramidal shapes for time periodic Lotka–Volterra competition–diffusion system in R N with N ≥ 3 . It should be mentioned that the existence, uniqueness and stability of two-dimensional time periodic traveling curved fronts of time periodic Lotka–Volterra competition–diffusion system in R 2 have been studied yet. By the supersolution and subsolution technique coupled with comparison principle, in this paper we construct the existence, non-existence and qualitative properties of time periodic pyramidal traveling front solutions for time periodic Lotka–Volterra competition–diffusion system in R N .